Effects of Amaferm® (Aspergillus oryzae fermentation extract) on performance and body temperature of stockers fed diets with or without fescue endophyte - Coffey, K.P.; Brazle, F.K.; Moyer, Joseph L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty-four stocker steers were offered endophyte-free fescue hay ad libitum, with either bromegrass or high-endophyte fescue seed screenings and supplements with or without Amaferm8 (Aspergillus oryzae fermentation extract). Steers offered bromegrass seed screenings gained faster (P<.01), consumed more feed (P<.01), and converted feed dry matter to gain more efficiently (P<.01) than those fed fescue seed screenings. Amaferm did not affect stocker performance or reduce rectal temperature. Therefore, feeding high-endophyte fescue screenings reduced intake and daily gain, and Amaferm did not offset those effects.
Keywords: Beef; Amaferm®; Aspergillus oryzae; Fescue; Endophyte; Stockers